Characterization of Livelihood Systems in Coral Ecosystem - Anshida Beevi; Monika Wason (Indian Journal of Extension Education, 2015)
A livelihood comprises the capabilities, assets and activities required for a means of living. The present study has undertaken to characterize the livelihood systems in coral islands of India. Out of 11 inhabiting islands of Lakshadweep, two islands “Kalpeni” and “Andrott” were selected for the study. From the islands selected, two wards and from each ward 30 individuals were selected by simple random sampling technique. A total of 120 respondents comprised the sample. The results showed that three livelihood groups in the study area include the farming alone (group 1), non-farm activities alone (group 2) and both farm and non- farm activities (group 3). Activity ranking exercise was done based on different activities carried out by the islanders for means of living. It shows that group 3 is engaged in more diversified activities as their livelihood source.